Bunuel wrote:

If a is a positive integer then 3^(2a) + 36^a/2^(2a) =

A. (9/4)^a + 9^a

B. 9^a + 18^a

C. 18^a

D. 0

E. 2 × 9^a

Kudos for a correct solution.

I am quoting the same question with a bit more formatting:

\(3^{2a} + \frac{36^a}{2^{2a}}\) ----> Let go of the variables and plug in a =1 as this statement must be true for all values of a (even 0).

Thus with a =1 we get, \(3^{2} + \frac{36^1}{2^{2}}\) = 2* 9 =18---> Now plug in a =1 in the options and we see that options C and E satisfy this. To eliminate C, use a =0. Thus E is the correct answer.